Design and Research of Skin Injection Molded TPE Materials Based on Genetic Algorithm. (29th February 2020) - Yan, Kui; Chen, Yizhe; Wang, Hui; Gao, Cheng; Bai, Qiuyang
Abstract : Thermoplastic elastomer (TPE) is a kind of new automotive interior material with high elasticity and strength. Traditional TPE materials were difficult to meet the new requirements of large-scale automotive interior parts with complex shape. In this study, the TPE material was prepared using different mass ratios with homopolymer polypropylene (PP), styrene-ethylene/butene-styrene copolymer (SEBS), naphthene oil (NO), magnesium stearate (MGST), and polytetrafluoroethylene (PTFE). A quality-prediction and multiobjective optimization method based on a genetic algorithm was applied. The parameters that had an important effect on the forming quality were selected using an orthogonal testing method. Results showed that using the proposed method, a new TPE material is obtained with excellent scratch resistance ability and high MFI. The mechanisms of the addition of PTFE and MGST were analysed according to SEM images. The peel strength of the optimized part was measured to prove the coating quality of TPE material.